Need for consistency in Nigerias agricultural development policy and programmes - Okigbo, B.N. (1985)
Consistency in agricultural development policy and programs is tantamount to adherence to guiding principles (policy), strategies or tactics and programs that are compatible with the nature of agriculture, problems to be solved and objectives desired. Based on the location specificity of agricultural production as bio-economic activity, defined as the science, business and art of growing crops and rearing animals to satisfy man's need for food, miscellaneous products and objectives, consistency also implies adoption of policies, strategies and programs that are compatible with prevailing ecological conditions and socio-economic melieu in target areas for agrcultural development. ...